Model MODEL MODERASI BERAGAMA PADA BUKU TEKS: STUDI ANALISIS PADA BUKU TEKS TK B - Abdurrohman, Asep - (Moderatio: Jurnal Moderasi Beragama, 2023)
This study aims to find out and analyze the extent to which the religious moderation model was developed by the author of TK B textbooks. Researchers used library research with qualitative research as a type of research. Sources of data studied, namely; Kindergarten B textbooks totaled seven books. To examine the text and images contained in TK B textbooks, researchers used Content Analysis. Content Analysis is a scientific analysis of the contents of a communication message. Technically, the scope of content analysis substance includes; classification of signs used in communication, using criteria as a basis for classification, and using certain analytical techniques as predictors. The results showed that the religious moderation model in TK B textbooks was introduced through local wisdom and national commitment. Local wisdom is represented by; relics of the past, such as; temples, statues, chariot wheels, jugs, pinisi boats, swords, temple gates, temple banners, traditional houses, traditional dances, traditional clothes, and names based on local traditions. While the national commitment is represented by the red and white flag and its pole, flag ceremonial activities, and the Garuda bird in the palace. But on the other hand, accommodating music playing as a symbol of a unifying tool for the nation and prevention of national disintegration. traditional dances, traditional clothing, and local tradition-based names. While the national commitment is represented by the red and white flag and its pole, flag ceremonial activities, and the Garuda bird in the palace. But on the other hand, accommodating music playing as a symbol of a unifying tool for the nation and prevention of national disintegration. traditional dances, traditional clothing, and local tradition-based names. While the national commitment is represented by the red and white flag and its pole, flag ceremonial activities, and the Garuda bird in the palace. But on the other hand, accommodating music playing as a symbol of a unifying tool for the nation and prevention of national disintegration.